Analysis of PCK Changes in Prospective Biology Teachers (International Journal of Psychosocial Rehabilitation, 2020)
Objectives—This study aims to analyze changes in PCK (Pedagogical Content Knowledge) prospective biology teachers at one private university in Kuningan District, West Java Province, Indonesia.Methodology—This research uses mixed methods through a concurrent embedded strategy. Quantitative methods are used to obtain a picture of the pattern of PCK changes in biology students in the even semester of the 2018/2019 academic year. Qualitative methods are used to get more data around these change patterns. The sample in this study was Biology Education students at one of the private tertiary institutions in West Java who participated in the study and participated in all research instruments and had complete data, namely 22 second semester students, 18 fourth semester students, 18 semester six students, and semester eight numbered 21 people, so that the number of valid samples amounted to 80 (77.7%) of the population of 103 students. The sampling technique used was purposive sampling and saturated samples. The instruments used were knowledge tests, Content Representation (CoRe), concept maps, questionnaires, and interviews.Findings: The results of the study show that 1) PCK is not only knowledge but also skill, so it requires multiple assessments to uncover it; 2) PCK as knowledge has a pattern of change that is not linear with the number of semesters that have been taken by prospective teacher students, in contrast to PCK as a skill; 3) PCK prospective teachers begin to grow when prospective teachers have obtained all pedagogical courses, namely the fourth semester; 4) PCK prospective teachers begin to develop clearly after prospective teachers take microteaching courses, namely the sixth semester; 5) PCK teacher candidates in the eighth semester already have an almost perfect form.Significance—The findings of the research result are significant in the LPTK (educational institutions and education personnel) curriculum structure changes regarding the distribution and number of courses included in the proportion of content and pedagogy families, the pattern of course debriefing programs, especially pedagogical families, and the patterns of planning, implementation, and evaluation of microteaching and PPL (practice field experience). The research findings successfully detected the initial changes and development of PCK and the form of PCK that was almost intact.